Network coordination of customer experience through customer and supplier involvement - Raitaluoto, Teemu (My University, 2017)
Customer experience has risen on top of marketing and management research. According to recent research, the industry expects to compete mainly through customer experience management. Benefits of a good customer experience include decreased customer churn, increased recommendation, and increased customer loyalty. These behaviors affect the revenue and costs of the company. Simultaneously, service delivery has become more fragmented than ever as companies outsource parts of the service to specialized organizations. Service delivery fragmentation leads to dispersed customer experience where control over the experience is low and uncertainty high. This research studies customer experience coordination in networks through customer and supplier involvement. Customer experience is coordinated as information about the experience is gathered from customers through service development involvement. Similarly, suppliers are involved to gather essential insights about partner-owned touch points. This information is shared with the network suppliers to create better and unified customer experience. The research was conducted as a single case study using qualitative methods such as semi-structured interviews. The case company is a large Finnish financial group operating in the healthcare sector. The findings indicate that customer experience can be coordinated through a combination of network types, while customers and suppliers are involved through pilot studies, surveys, and interviews. The coordination task can be given to an administrative organization, which coordinates the experience on behalf of the network, while participating in development initiatives with other network members.
Keywords: Customer experience; CEM; customer involvement; supplier involvement; customer journey; network management; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|